Planting composition for visual quality of green campus environment / Norizan Mt Akhir ... [et al.] - Mt Akhir, Norizan; Md Sakip, Siti Rasidah; Abbas, Mohamed Yusoff; Othman, Noriah (2018)
Campus landscape is an everyday life experience for students. But, do students perceive the landscape in every space within the campus? Proximity and access to green spaces on campus are related to how they perceive the campus environment. The aim of this study was to understand the assessment of planting composition pattern through objectivist and subjectivist paradigm which is useful for campus landscape development. Planting design as critical component contributes to the overall design concept and objectives, and this is achieved by spatial design and by the themes employed in detailed planting composition in the campus as well as shaping the outdoor campus spaces. However, planting composition is rarely issued in landscape assessment study. The landscape visual quality assessment is significant to achieve the aim in order to gain the appropriate pattern or layout of planting that is most preferable by students. The evaluation of this quality can be both objectively (physical) and subjectively (psychology). Both these paradigms can guide the researcher to identify the existing pattern and preferred planting design that is able to satisfy the students‟ needs. Physical factors of plants only help in identifying the pattern and visual properties but, the psychological factors can open to different possibilities of results in landscape quality assessment. Therefore, the recognition of the relationship between planting composition and students‟ preferences should be established as to bring a new model of green campus environment at the university.